Organoids at the PUB: The Porcine Urinary Bladder Serves as a Pancreatic Niche for Advanced Cancer Modeling. Issue 11 (18th February 2022) - Melzer, Michael Karl; Breunig, Markus; Arnold, Frank; Wezel, Felix; Azoitei, Anca; Roger, Elodie; Krüger, Jana; Merkle, Jessica; Schütte, Lena; Resheq, Yazid; Hänle, Mark; Zehe, Viktor; et al.
Abstract: Despite intensive research and progress in personalized medicine, pancreatic ductal adenocarcinoma remains one of the deadliest cancer entities. Pancreatic duct‐like organoids (PDLOs) derived from human pluripotent stem cells (PSCs) or pancreatic cancer patient‐derived organoids (PDOs) provide unique tools to study early and late stage dysplasia and to foster personalized medicine. However, such advanced systems are neither rapidly nor easily accessible and require an in vivo niche to study tumor formation and interaction with the stroma. Here, the establishment of the porcine urinary bladder (PUB) is revealed as an advanced organ culture model for shaping an ex vivo pancreatic niche. This model allows pancreatic progenitor cells to enter the ductal and endocrine lineages, while PDLOs further mature into duct‐like tissue. Accordingly, the PUB offers an ex vivo platform for earliest pancreatic dysplasia and cancer if PDLOs feature KRAS G12D mutations. Finally, it is demonstrated that PDOs‐on‐PUB i) resemble primary pancreatic cancer, ii) preserve cancer subtypes, iii) enable the study of niche epithelial crosstalk by spiking in pancreatic stellate and immune cells into the grafts, and finally iv) allow drug testing. In summary, the PUB advances the existing pancreatic cancer models by adding feasibility, complexity, and customization at low cost and high flexibility. Abstract : The porcine urinary bladder is optimized as an easy‐to‐handle and cost‐efficient scaffold for the engraftment and maturation of various pancreatic cell types for advanced cancer modeling. Stem cell‐derived pancreatic duct‐like cells demonstrate enhanced maturation and, in addition, papillary tumor growth upon oncogene stimulation. Finally, patient‐derived organoids and pancreatic stellate cells develop into complex tumors on the porcine urinary bladder.